2011
DOI: 10.1007/s10461-011-0022-z
|View full text |Cite
|
Sign up to set email alerts
|

Male Migration/Mobility and HIV Among Married Couples: Cross-Sectional Analysis of Nationally Representative Data from India

Abstract: This paper examines the associations between male migration and mobility with HIV among married couples in India. Cross-sectional analyses of a nationally representative household survey conducted across all 29 states of India from 2005 to 2006 via the National Family Health Survey-3 (NFHS-3) included a subsample of 27,771 married couples who were tested for HIV as a part of their participation. Both bi-variate and multi-variate analyses were conducted. About 0.5% of the total married couples in the current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…For many years the predominant model was that a male migrant worker would acquire HIV from unprotected sex with partners while abroad, and transmit the virus to his wife or other partners at home when he returned. Indeed this pattern has been observed in numerous studies, for example in South Africa (Campbell, ) and in India (Saggurti et al, ). In every population, condom use for HIV and STI protection is more contentious and less frequent among intimate partners (e.g.…”
Section: Hiv Risk and Vulnerability During The Mobility Processsupporting
confidence: 64%
See 1 more Smart Citation
“…For many years the predominant model was that a male migrant worker would acquire HIV from unprotected sex with partners while abroad, and transmit the virus to his wife or other partners at home when he returned. Indeed this pattern has been observed in numerous studies, for example in South Africa (Campbell, ) and in India (Saggurti et al, ). In every population, condom use for HIV and STI protection is more contentious and less frequent among intimate partners (e.g.…”
Section: Hiv Risk and Vulnerability During The Mobility Processsupporting
confidence: 64%
“…married couples) than with casual partners or sex workers (Gardner et al, 1999). As for migrants, a classic study from rural Mexico showed that although wives of men temporarily working in the United States were aware of the risks, traditional gender roles prevented them from using condoms when their husbands returned home to visit (Salgado de Snyder et al, 1996). Some 15 years later, and on a different continent, researchers came to much the same finding: Tajik wives of men working in Moscow never used condoms, never suggested doing so, and found it shameful to discuss such things (Golobof et al, 2011).…”
Section: In Communities Of Return/originmentioning
confidence: 99%
“…The regular sexual partners of high-risk males, such as migrants and injecting drug users (IDUs), are at elevated risk for HIV [9,10]. Evidence has shown, for example, that women with a migrant husband are more than two times more likely to be HIV-positive than those with a non-migrant husband [7], and monogamous non-injecting spouses of IDUs are ten times more likely to be HIV-positive than general population women [11].…”
Section: Introductionmentioning
confidence: 99%
“…Few other studies also reported a higher percentage of widowed and separated FSWs (Dandona et al, 2005). Another study revealed that poverty was the main reason for women coming to this profession in addition to other factors such as lack of education, financial freedom, domestic violence, family responsibility, lack of support by family members, harassment and abuse in society and in workplace (Saggurti et al, 2011). The national BSS in 2006 also revealed that women often get involved in sex work due to poverty, marital breakup (NACO, 2006).…”
Section: Discussionmentioning
confidence: 96%